2007
DOI: 10.1152/ajpheart.00487.2006
|View full text |Cite
|
Sign up to set email alerts
|

Immune suppression prevents renal damage and dysfunction and reduces arterial pressure in salt-sensitive hypertension

Abstract: Tian N, Gu JW, Jordan S, Rose RA, Hughson MD, Manning RD Jr. Immune suppression prevents renal damage and dysfunction and reduces arterial pressure in salt-sensitive hypertension. Am J Physiol Heart Circ Physiol 292: H1018 -H1025, 2007. First published October 13, 2006; doi:10.1152/ajpheart.00487.2006.-The goal of this study was to test the hypothesis that renal infiltration of immune cells in Dahl S rats on increased dietary sodium intake contributes to the progression of renal damage, decreases in renal hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 32 publications
(46 reference statements)
7
69
0
3
Order By: Relevance
“…Finally, a recent cross-sectional study found that highdietary salt intake was associated with both increased albuminuria and C-reactive protein in treated patients with hypertension (43), suggesting that inflammatory mechanisms might also be involved in the nephrotoxic effect of excess salt intake (44,45).…”
Section: Possible Mechanisms Of the Effect Of Sodium Intake Reductionmentioning
confidence: 99%
“…Finally, a recent cross-sectional study found that highdietary salt intake was associated with both increased albuminuria and C-reactive protein in treated patients with hypertension (43), suggesting that inflammatory mechanisms might also be involved in the nephrotoxic effect of excess salt intake (44,45).…”
Section: Possible Mechanisms Of the Effect Of Sodium Intake Reductionmentioning
confidence: 99%
“…8,9 Inflammatory mechanisms have been proposed to have a role in this nephrotoxic effect of salt excess. [9][10][11][12][13] The role of inflammation in the initiation and progression of cardiovascular diseases is increasingly recognized. 14,15 Studies in hypertensive individuals have shown increased plasma and vascular tissue levels of C-reactive protein (CRP) and several inflammatory cytokines, suggesting a potential association between vascular inflammation and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…High circulating IL6, TNF-α, IL8 and MCP1 were detected in a cross-sectional study of 275 stable hypertensive patients with or without HFpEF [48]. In salt sensitive hypertension, high salt intake leads to systemic oxidative stress [101] possibly because of renal production of proinflammatory cytokines [102]. The RAAS is a major activator of NADPH oxidase and reactive oxygen species (ROS) production and increasing evidence reveals that the RAAS is importantly involved in linking obesity, metabolic syndrome, insulin resistance (IR), chronic kidney disease and hypertension [103].…”
Section: Hypertensionmentioning
confidence: 99%